The Experience of Unemployment in Young People./An Interpretive Phenomenological Analysis. - Lamproukou Markella; Zafeiraki Anna (2016)
Introduction, Method, Design, Epistemology, Idiography, Participants, Data Collection, IPA Steps, Analysis, Social Racism of Others and Social Exclusion, Transition to Unemployment - Stages, Shock, Denial, Anger, Depression, Acceptance, the Negative Impact of Unemployment. Losing your Known Identity, Loss of Self - Esteem, the Experience of Negative Emotions, Discussion, Reflexivity, Appendix.